2017
DOI: 10.1002/app.45312
|View full text |Cite|
|
Sign up to set email alerts
|

Oxaliplatin‐loaded crosslinked polymeric network of chondroitin sulfate‐co‐poly(methacrylic acid) for colorectal cancer: Its toxicological evaluation

Abstract: The purpose of this study was to develop and characterize chemically crosslinked chondroitin sulfate-co-poly(methacrylic acid) (CSMA) hydrogels for colon targeting of oxaliplatin (OXP) to treat colorectal cancer. CSMA hydrogels were synthesized by freeradical polymerization. Chondroitin sulfate was chemically crosslinked with methacrylic acid in an aqueous medium. Ammonium peroxodisulfate and N,N-methylene bisacrylamide were used as the initiator and crosslinker, respectively. Fourier transform infrared spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 50 publications
(19 citation statements)
references
References 38 publications
4
15
0
Order By: Relevance
“…The above discussion indicates that fabricated hydrogels have higher thermal stability than unreacted ASP and AL and could be employed for controlled drug delivery system. Barkat et al (2017) prepared chondroitin sulfate-based hydrogels and reported maximum thermal stability for the prepared network of hydrogels compared to hydrogels contents [50], which further supports our observation.…”
Section: Dsc Analysissupporting
confidence: 81%
See 1 more Smart Citation
“…The above discussion indicates that fabricated hydrogels have higher thermal stability than unreacted ASP and AL and could be employed for controlled drug delivery system. Barkat et al (2017) prepared chondroitin sulfate-based hydrogels and reported maximum thermal stability for the prepared network of hydrogels compared to hydrogels contents [50], which further supports our observation.…”
Section: Dsc Analysissupporting
confidence: 81%
“…Similarly, two endothermic peaks at 63 and 268 °C are assigned by DSC of AL ( Figure 6 B) while an exothermic peak is detected at 237 °C, respectively. The endothermic peaks are concerned with water loss related to hydrophilic groups whereas exothermic peak shows the dehydration and depolymerization reactions [ 49 ]. DSC thermogram of ASP/ALPAA hydrogels ( Figure 6 C) reveals endothermic and exothermic peaks at 225, 330 and 170, 252 °C, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The thermal degradation of the developed network starts at 370 °C, which indicates that the thermal stability of the SPSPAA hydrogel is higher than unreacted polymer. Barkat et al prepared chondroitin sulfate-based hydrogels and reported higher thermal stability for the developed system compared to polymer [ 32 ]. Figure 4 C indicates the DSC thermogram of KT.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, a minor exothermic peak is perceived at 253 °C, followed by the glass phase transition. The discussion shows that the thermal degradation of the fabricated hydrogel networks is perceived within the temperature range of 350–400 °C, indicating higher stability of the fabricated hydrogels compared to CP and SpS [ 47 ].…”
Section: Resultsmentioning
confidence: 99%